Defining Impact of a Rapid Response Team: Qualitative Study with Nurses, Physicians, and Hospital Administrators - Benin, Andrea L. (2012)
The objective of this study was to qualitatively describe the impact of a Rapid Response Team (RRT) at a 944-bed, university-affiliated hospital. We analyzed 49 open-ended interviews with administrators, primary team attending physicians, trainees, RRT attending hospitalists, staff nurses, nurses, respiratory technicians. Themes elicited were categorized into the domains of (1) morale and teamwork, (2) education, (3) workload, (4) patient-care, and (5) hospital-administration. Positive implications beyond improved care for acutely ill patients were: increased morale and empowerment among nurses, real-time redistribution of workload for nurses (reducing neglect of non-acutely ill patients during emergencies), and immediate access to expert help. Negative implications were: increased tensions between nurses and physician-teams, a burden on hospitalist RRT-members, and reduced autonomy for trainees. The RRT provides advantages that extend well beyond a reduction in rates of transfers to intensive care units or codes but are balanced by certain disadvantages. Potential impact from these multiple sources should be evaluated to understand the utility of any RRT program.